ANALISA DAMPAK KEBIJAKAN TAX AMNESTY DAN TINGKAT KEPATUHAN WAJIB PAJAK TERHADAP PENINGKATAN PENERIMAAN NEGARA - Ulaila Ulaila (Jurnal Akuntansi Indonesia, 2018)
Abstract : This study aims to determine whether the Tax Amnesty Policy and tax compliance has a significant effect on state revenues. Tax Amnesty is the government's attempt to increase state revenue. Taxpayer Compliance in implementing tax obligations are also indicators of tax revenues. Amnesty Tax policy takes the form of a waiver countries to collect taxes that should be owed. The research sample derived from data Directorate General of Taxes, Ministry of Finance of the Republic of Indonesia in this 2016.This Study approach qualitative method to collect data. Samples of this study were obtained from the primary data and secondary data, surveys, observations, and interviews. These results indicate that the Tax Amnesty and Taxpayer Compliance positive effect on state revenue.